GROUNDWATER QUALITY ASSESSMENT FOR DRINKING AND IRRIGATION ON HINDUPUR MANDAL, ANANTAPUR DISTRICT, ANDHRA PRADESH STATE, SOUTH INDIA. - Y. Krunakar; Rao, Y. HPM Mohana Prasada; U. Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Groundwater serves as a critical resource for drinking and irrigation, particularly in arid and semi-arid regions like Hindupur Mandal, Andhra Pradesh, where surface water availability is limited. This study assesses the hydrogeochemical characteristics and seasonal variations in groundwater quality using 25 samples collected during pre- and post-monsoon periods. Physicochemical parameters including pH, EC, TDS, major cations and anions, and various irrigation indices such as SAR and %Na were analyzed and compared against WHO and BIS standards. Spatial distribution maps, Piper plots, and USSL diagrams were utilized to interpret water chemistry, facies distribution, and irrigation suitability. Results indicate that groundwater is predominantly of Na–Cl type during the pre-monsoon and shifts partially toward Ca–Mg–HCO₃ type post-monsoon, reflecting seasonal dilution from rainfall recharge and carbonate weathering. While the majority of samples fall within acceptable limits for both drinking and irrigation, elevated concentrations of Na⁺, K⁺, and Cl⁻ in certain locations point to anthropogenic impacts such as agricultural runoff and domestic wastewater infiltration. The study concludes that groundwater quality in the area is generally acceptable for domestic and agricultural use, though periodic monitoring is essential to manage contamination risks and ensure sustainable use.